No longer male and female: interpreting Galatians 3:28 in early Christianity - Hogan, Pauline Nigh (Library of New Testament studies, 2008)
This is a historical-critical exploration of the post-New Testament career of the verse Galatians 3:28.Galatians 3:28, in particular the phrase, "There is...no longer male and female; for you all are one in Christ Jesus," would seem to point towards an ethos of gender equality among Christians. Acting on this assumption, a number of scholars have considered the phrase significant in reconstructing attitudes towards women in early Christianity. Until now, however, a study of the history of interpretation of Gal 3:28 has been lacking. The exploration of the post-New Testament career of the verse is therefore the focus of this book. The approach is historical-critical, discussing the exegesis of Gal 3:28 in the context of attitudes about the roles of women in the first four centuries CE.This study reveals that early Christians did not always approach this verse with the same concerns as modern readers. Ancient commentators brought several different questions to their discussion of Gal 3:28, and it is impossible to discover the trajectory in exegesis of this verse that might have been expected.It becomes apparent that during the first four centuries of Christianity most writers treated Gal 3:28 as a statement about the identification of Christians with Christ and therefore an indication that in the resolution of various differences into unity, they could achieve an ideal state.